Integrated Weed Management in Transplanted Chilli Under Irrig,ated Conditions of Arid Zone - Yadav, R S (Annals of Arid Zone, 2016)
An investigation was carried out to evaluate effect of integrated methods of weed control on weeds and their effect on chilli (Capsicum allllum L.) yield during 1993-94 and 1995-96. Among the weed control treatments, oxyf1ourfen at 0.2 kg ha,I or pendimethalin at 1.0 kg ha-I supplement with two hoeings at 30 and 60 days after transplanting (DAT) significantly reduced the dry weight of grassy as well as. broad-leaved weeds compared to oxyf1ourfen at 0.3 kg ha-I alone or supplement with one hoeing at 30 DAT. Oxyf1ourfen (0.2 to 0.3 kg ha-I) or pendimethalin (1.0 kg ha,I) when integrated with one or two weedings produced significantly higher dry chilli yield compared to herbicide alone (oxyflourfen at 0.3 kg ha- Highest benefit:cost ratio was also obtained in oxyf1ourfen at 0.2 kg ha-I supplementÂ· with two hoeings at 30 and 60 DAT.